Differential pharmacology and clinical utility of long-acting bronchodilators in COPD – focus on olodaterol - Matera MG; Ora J; Cazzola M (Dove Medical Press, 2015)
Maria Gabriella Matera,1 Josuel Ora,2 Mario Cazzola2,3 1Department of Experimental Medicine, Unit of Pharmacology, Second University of Naples, Naples, 2Division of Respiratory Medicine, University Hospital Tor Vergata, 3Department of Systems Medicine, Respiratory Pharmacology Research Unit, University of Rome Tor Vergata, Rome, Italy Abstract: Olodaterol (BI 1744 CL) is a novel, once-daily long-acting β2-agonist (LABA) designed with the aim of improving β2-adrenoreceptor selectivity and intrinsic activity. Phase III pivotal trials have documented that olodaterol Respimat Soft Mist inhaler 5 µg induces fast onset of bronchodilation, comparable with formoterol at day 1. Moreover, significant lung function improvements have been documented up to 48 weeks in patients with moderate to very severe chronic obstructive pulmonary disease (COPD). Olodaterol was generally well tolerated and had an acceptable cardiovascular and respiratory adverse event profile. Regrettably, the clinical development of olodaterol is however still too partial to draw any firm conclusions on the positioning of this ultra-LABA as monotherapy in the management of COPD. Waiting for further data on the impact of olodaterol on different patient-reported outcomes, which however are widely available for indacaterol, and mainly for a head-to-head comparison between these two ultra-LABAs and between olodaterol long-acting antimuscarinic antagonists other than tiotropium, we believe it is correct to follow the clinical indications of indacaterol also for olodaterol. In any case, the parallel bronchodilating modes of action of olodaterol and tiotropium make them an attractive combination in COPD. The results from the ongoing large TOviTO Phase III trial program have documented the efficacy and safety of olodaterol/tiotropium fixed-dose combination as maintenance therapy in patients with moderate to very severe COPD. In particular, olodaterol/tiotropium fixed-dose combination provides a convincing alternative for patients remaining symptomatic with olodaterol monotherapy. Keywords: olodaterol, β2-agonists, once-daily dose, chronic obstructive pulmonary disease